Follow-up care in general practice of patients with myocardial infarction or angina pectoris: initial results of the SHIP trial. Southampton Heart Integrated Care Project. - Jolly, K; Bradley, F; Sharp, S; Smith, H; Mant, D (1998)
OBJECTIVE: We aimed to assess the effectiveness of a nurse-led programme to ensure that follow-up care is provided in general practice after hospital diagnosis of myocardial infarction (MI) or angina pectoris. METHODS: We conducted a randomized controlled trial with stratified random allocation of practices to intervention and control groups within all 67 practices in Southampton and South-West Hampshire, England. The subjects were 422 adult patients with a MI and 175 patients with a new diagnosis of angina recruited during hospital admission or chest pain clinic attendance between April 1995 and September 1996. Intervention involved a programme of secondary preventive care led by specialist liaison nurses in which we sought to improve communication between hospital and general practice and to encourage general practice nurses to provide structured follow-up. The main outcome measures were: extent of general practice follow-up; attendance for cardiac rehabilitation; medication prescribed at hospital discharge; self-reported smoking, diet and exercise; and symptoms of chest pain and shortness of breath. Follow-ups of 90.1 % of subjects at 1 month and 80.6% at 4 months were carried out. RESULTS: Median attendance for nurse follow-up in the 4 months following diagnosis was 3 (IQR 2-5) in intervention practices and 0 (IQR 0-1) in control practices; the median number of visits to a doctor was the same in both groups. At hospital discharge, levels of prescribing of preventive medication were low in both intervention and control groups: aspirin 77 versus 74% (P = 0.32), cholesterol lowering agents 9 versus 10% (P = 0.8). Conversely, 1 month after diagnosis, the vast majority of patients in both groups reported healthy lifestyles: 90 versus 84% reported eating healthy food (P = 0.53); 73 versus 67% taking regular exercise (P = 0.13); 89 versus 92% not smoking (P = 0.77). Take up of cardiac rehabilitation was 37% in the intervention group and 22% in the control group (P = 0.001); the median number of sessions attended was also higher (5 versus 3 out of 6). CONCLUSIONS: The intervention of a liaison nurse is effective in ensuring that general practice nurses follow-up patients after hospital discharge. It does not alter the number of follow-up visits made by the patient to the doctor. Levels of prescribing and reported changes in behaviour at hospital discharge indicate that the main tasks facing practice nurses during follow-up are to help patients to sustain changes in behaviour, to encourage doctors to prescribe appropriate medication and to encourage patients to adhere to medication while returning to an active life. These are very different tasks to those traditionally undertaken by practice nurses in relation to primary prevention, where the emphasis has been on identifying risk and motivating change. Assessment of the effectiveness of practice nurses in undertaking these new tasks requires a longer follow-up.